(untitled) (Research, Society and Development, 2021)
Sustainable development of agricultural systems is based on the planning and management of natural resources, so it is essential to know the landscape features. In view of the above, the present work aims to provide information on the hydrogeomorphometric characteristics of the Mutum river microbasin. The landscape analysis was performed with the Google Earth, QGIS and TrackMaker Free software, altimetric images from the Alos satellites, and data from the literature. The microbasin has an area of ​​8.64 km2, a perimeter of 15.26 km, elongated formations and low to medium susceptibility to flooding (geometric point of view), altitudes from 228 to 322 m, predominance of smooth wavy (50.81% ) and wavy reliefs (30.67%), 92.93% of its area with low propensity to influence the spread of fires and 92.94% suitable for apt agricultural mechanization, drainage network of 17.30 km with dendritic pattern 4th order, average spring densities, average drainage density, maintenance coefficient of 499.4 m2 m-1, straight main channel and low concentration time. The microbasin has the potential for agricultural development, however, the adoption of conservationist soil management practices is necessary to mitigate the impacts of this activity on the environment. We recommend a study on the spatial and temporal dynamics of land cover, to analyze the quality and quantity of native vegetation in the microbasin, and thus, delimit priority areas for the maintenance and/or recovery of this vegetation.